(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The proposed scientific article examines the theoretical and methodological aspects of literacy education as the basis for overcoming illiteracy in the period of globalization.Based on the results of the conducted research, the meaning and content of literacy, its place in human life, the impact of quality education on illiteracy, problems and ways to solve it, the most important education in our nation were proposed. In the development of the education system, teachers increase their professional level, if technical means are used correctly, and teaching methods are used correctly, the quality will.